Regional Digital MSME Ecosystems, Tax Compliance, and Fiscal Contribution in the Special Region of Yogyakarta (DIY): Mediating Role of Tax Literacy and Financial Inclusion - Muh Adzam; Kadari Kadari; Fajar Aribowo; Erwan Sutrisno (Journal The Winners, 2026)
This research examined the role of a regional digital micro, small, and medium enterprises (MSMEs) ecosystem in shaping tax compliance and fiscal contribution among micro, small, and medium enterprises in the Special Region of Yogyakarta (DIY), with particular attention to the mediating roles of tax literacy and financial inclusion. Focusing on the SBJ platform as a government-led digital intervention, this research adopted a quantitative approach to analyze how engagement with a regional digital ecosystem influences MSMEs’ fiscal-related behavior and business outcomes. The findings indicate that the use of SBJ strengthens MSMEs’ understanding of taxation and improves access to formal financial services, both of which are essential foundations for encouraging business formality. Enhanced business formality emerges as a critical gateway to the formal fiscal system, reinforcing compliance-oriented behavior through improved administrative discipline, transaction transparency, and institutional integration. As MSMEs become more compliant with tax obligations, their fiscal contribution and business performance improve through greater financial credibility, operational stability, and access to broader economic opportunities. Importantly, the influence of the digital ecosystem on fiscal contribution operates through an indirect and sequential pathway, in which tax literacy and financial inclusion facilitate the transition from digital engagement to business formalization and sustained tax compliance. These findings position SBJ not merely as a digital MSME support platform but as a strategic regional fiscal policy instrument that integrates digital governance with local revenue enhancement and MSME empowerment.